Dicotyledons: Rosids - Eggli, Urs.; Nyffeler, Reto. (Cham : Springer International Publishing : Imprint: Springer, 2023)
The succulent species of the families of subclass Rosidae are presented by alphabet of families, genera, and species, with comprehensive listings of synonyms added at all levels. Detailed descriptions are given for all accepted taxa, together with data on the distribution and typification, and references to the most important literature. Where necessary, information on ecology, ethnobotany, history, etc. is added, and in many places, proposed relationships are critically discussed. The volume covers the succulents from the families Anacardiacae, Begoniaceae, Bixaceae, Brassicaceae, Burseraceae, Capparaceae, Caricaceae, Clusiaceae, Cucurbitaceae, Euphorbiaceae, Fabaceae, Francoaceae, Geraniaceae, Malvaceae, Melastomataceae, Meliaceae, Moraceae, Moringaceae, Oxalidaceae, Passifloraceae, Sapindaceae, Tropaeolaceae, Urticaceae, Vitaceae and Zygophyllaceae.
Keywords: Botany; Plant anatomy; Plants -- Development; Plant Science; Plant Anatomy and Morphology; Plant Development